The Evolving Role Of Nursing Technicians: Contributions To Patient Care And Healthcare Teams (Journal of Namibian Studies : History Politics Culture, 2022)
The role of nurse technicians in healthcare team and in delivering patient care is constantly changing along with the healthcare landscape. The perception of nurse technicians as nothing more than medical assistants is long gone. Whereas, Nurse technicians today contribute significantly to the overall patient experience and play a vital and dynamic role in shaping healthcare outcomes. Also, Nurse technicians have emerged as important figures in the provision of patient- individualized care due to their holistic approach, empathy, and clinical expertise. the Increased autonomy and decision-making power are hallmarks of nurse technicians' changing roles in patient care. Nurse technicians are now actively participating in the coordination, evaluation, and planning of care rather than being restricted to adhering to rigid protocols. However, presence of nurse technician educator or learning programs is beneficial in improving nurse technicians’ roles and contributions in health team and communication strategies, ultimately, enhance nursing technicians’ care. The purpose of this review of literature is to evaluate the role of nurse technicians in healthcare team in contribution to patient care.